Beliefs around help-Seeking and Support for Dementia in the Australian Arabic Speaking Community. (July 2023) - Allam, Issra; Gresham, Meredith; Phillipson, Lyn; Brodaty, Henry; Low, Lee-Fay
Background: The number of people with dementia in multicultural Australia is rapidly increasing. Despite its culturally diverse population, there is limited research about how people from ethnic minority groups understand and approach help-seeking and support for dementia. The aim of this study is to understand the perceptions of dementia symptoms, help-seeking and support in the Australian Arabic-speaking community. Methods: This study used a cross-sectional qualitative research design. Individual, semi-structured interviews using projective stimulus techniques were used. Participants were three Arabic-speaking people aged over 70 who were experiencing cognitive changes or dementia symptoms, six carers, and five health or social care practitioners experienced in working with Arab-Australians. Phone or video chat interviews were conducted in either Arabic or English. Interviews were audiotaped, translated when needed, transcribed verbatim and inductive thematic analysis was undertaken. Findings: Seven themes were identified. Participants described dementia as relating to symptoms of confusion and memory loss. Carers and older people believe that when older people are experiencing these cognitive symptoms, they must be cared for primarily by ensuring their happiness and comfort. Barriers to help-seeking and support included a lack of help-seeking due to cultural norms of family orientated care, families are unsure of where to seek help and fear of community judgement. Two ways to facilitate help-seeking and support were to build trust through culturally appropriate support and to educate the community. Conclusion: Family, trust and community were identified as central pillars of the Australian-Arabic-speaking community. There is a need to increase dementia literacy in this community particularly around help-seeking and decreasing stigma. Education should be promoted by trusted community members and religious leaders. As the first point of professional contact, general practitioners need to be upskilled to support Arabic-speaking Australians around dementia.